SOSIOLOGI LEMBAGA PENDIDIKAN SMK BERBASIS ISLAM: REPRODUKSI KELAS PEKERJA TERDIDIK MELALUI POLA MAGANG INDUSTRI (LINK AND MATCH) - Muh. Hanif; Anya Azzahra Arkania Mansyur (Jurnal Pendidikan Islam, 2026)
This study examines how the link-and-match industrial internship pattern in Islamic-based vocational schools systematically contributes to the reproduction of an educated working class. Using a qualitative case study approach at SMK Cokroaminoto Wanadadi, this study explores the relationship between the curriculum, internship programs, and graduates' employment. The primary focus is not only on job readiness but also how education shapes social positions upon entry into the workforce. The results show that the curriculum developed in collaboration with industry partners places greater emphasis on technical competencies. However, general competencies also receive a greater portion according to their level. Nevertheless, students are better prepared to meet the needs of the industrial workforce rather than developing the capacity to understand the broader work structure. Long-term internships condition the internalization of a habitus that emphasizes compliance with rules, work discipline, and acceptance of hierarchical authority. Vocational high school graduates are largely absorbed in general jobs due to the limited number of suitable jobs. This study concludes that vocational high schools, without critical awareness from all stakeholders, have the potential to become machines for the reproduction of an educated working class.